Recurrent encephalopathy?—no, i'm a sleeping beauty!!. (24th May 2012) - Iqbal, C; Prasad, M; Rittey, C
Abstract : Aim: To describe the clinical presentation of 'Kleine-Levin (sleeping beauty) syndrome' in a child, who presented with recurrent episodes consistent with encephalopathy, associated with excessive sleepiness, cognitive and behavioural disturbance and hyper sexuality. Method: We report a previously well 14 years old boy who following a viral throat infection presented acutely with excessive tiredness, sleeping excessively, abnormal behaviour and hypersexuality. On examination he was sleepy but easily arousable. His GCS (15/15) and rest of the neurological examination including fundoscopy and other systemic examination was completely unremarkable. All his initial investigation including electrolytes, LFTs, CSF, virology screen and MRI brain scan were normal. Detailed autoimmune screening including anti-NMDAR, potassium channel and anti-GAD antibodies were also negative. EEG showed non-specific diffuse slowing consistent with encephalopathy. His excessive sleepiness gradually improved together with his altered behaviour in about two weeks after presentation. Hyper sexuality became more overt during this phase manifesting as fiddling with his genitalia, putting his pant down in front of parents and even inappropriate behaviour towards female staff. All these symptoms completely disappeared three weeks after his presentation and he attended school as before. He was readmitted six weeks later with exactly similar presentation and again only positive result being diffuse non-specific slowing of EEG. His recovery was also similar and he was completely back to his normal self in three weeks time. Result: His recurrent symptoms are consistent with 'Kleine-Levin syndrome (KLS)' or 'sleeping beauty syndrome'. KLS is a rare disorder which mainly affects adolescent men. Common symptoms include hypersomnia (100%), cognitive changes (96%), eating disturbances (80%), hypersexuality, compulsions, and depressed mood. The syndrome usually lasts for 8 years, with on an average seven episode of 10 days each recurring every 3.5 months. It is most frequently precipitated by infections and somnolence decreases using stimulants in nearly 40% of cases. Conclusion: We believe neurologist and paediatricians should be aware of this (KLS) rare but distinct syndrome as early diagnosis will help us in reassuring patients and their families and will prevent unnecessary investigations.